Beyond the social: Cumulative implications of COVID-19 for first nations university students in Australia - Rebecca Bennett; Bep Uink; Sam Cross (Social Sciences & Humanities Open, 2020)
This position paper explores possible repercussions of the Corona Virus (COVID-19) response for Indigenous Australians in higher education. Focusing on Western Australian universities’ swift migration to online learning, halfway through a teaching semester, we identify risks at the intersection between educational and digital inequities, illustrated by author experiences working in an Indigenous Education Unit. Considering our observations of Indigenous students’ recent experiences, we argue that the pre-existing digital divide in Australia creates challenges for Indigenous university students, in addition to those faced by all university students coping with the transition to online learning in a context of social isolation. These include experiences of 1) cultural isolation, brought about by being – both physically and digitally – cut off from extended family, community, and Country and 2) digital isolation, brought about by inequitable access to the full range of digital infrastructure required for effective online learning. We argue that these intersecting layers of isolation highlight persistent inequities in Australian society and create new challenges for Indigenous university students. We appeal to universities to acknowledge and ameliorate culturally specific forms of isolation for Indigenous students, triggered through the complex combination of COVID-19 anxiety, the digital divide and educational minority status. Without this, we worry that the COVID-19 pandemic could reverse the global trend towards increasing Indigenous participation in university education and set-back efforts to Indigenise the university sector.